When love blossom: a campaign on pregnancy for the parents-to-be in Singapore. - Lim, Si Min. (2008)
This paper presents the collaboration between aLife and a group of three final-year students, Chen Jieting, Lim Si Min, and Mok Kai Lynn, from Wee Kim Wee School of Communication and Information, Nanyang Technological University (NTU). This communication campaign sets out to increase awareness and participation levels aLife and also impact the pregnancy scene in Singapore. Through measurement of the campaign’s total advertising equivalent value, the campaign has achieved substantial media coverage. This paper detailed our research that directed the communication plans, strategies and implementations for our campaign, and an evaluation of our efforts.